Diesel price hike and the energy squeeze on Pakistan's smallholder irrigators - Ul-Hassan, Mehmood; Shah, Tushaar; Ur Rehman, S.; Khattak, M.Z.; Tanwir, F.; Saboor, A.; Lashari, Bakhshal K. (2008)
The smallholder irrigators of Pakistan have been under squeeze due to rising energy costs, as they depend heavily on pump and tractor owners for irrigation water and agricultural operations. The recent trends of perpetual increase in the energy prices in general, and diesel prices in particular, have resulted into soaring operational costs of agricultural machinery, causing the pumps and tractor rentals to rise because of monopoly of pump owners in the informal village markets. This paper aims at bringing forth the impacts of successive diesel price increase on irrigation economy of smallholders, and their coping strategies to absorb the energy shocks and sustain their livelihoods. Based on a synthesis of qualitative assessment from 9 village level case studies carried out in NWFP, Punjab and Sindh provinces of Pakistan, where diesel and electric pumps are essential for sustaining irrigated agriculture, the paper confirms that the recent hike in diesel prices have proven to be the proverbial last straw on camel's back for the livelihoods of small farmers and tenants. While some landless tenants had quitted agriculture as a profession due in part to soaring diesel prices, the major coping strategies of the survivors were [a] switching the power source; [b] high input - high profit strategy; c) water conservation strategy; and d) agriculture exodus strategy. The paper also suggests areas for policy intervention and further research.